KEEFEKTIFAN MODEL THINK TALK WRITE (TTW) DALAM PEMBELAJARAN MENULIS SURAT PRIBADI PADA SISWA KELAS VII SMP NEGERI 24 SURABAYA - Fidiandini, Namira Restu; Suhartono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low personal letter writing skills of seventh-grade students of SMP Negeri 24 Surabaya, particularly in aspects of content, structure, capitalization, punctuation, and language. This study aims to describe the effect of the Think Talk Write (TTW) learning model on personal letter writing skills and the factors that influence its effectiveness. This study used a mixed methods study with a One Group Pretest-Posttest design. The sample consisted of 28 students of grades VII-F of SMP Negeri 24 Surabaya. Data collection techniques included pretests, posttests, observations, interviews, and questionnaires. The results showed that the average pretest score of 33.32 increased to 73.00 in the posttest. The paired sample t-test obtained a significance value of 0.000 < 0.05, indicating a significant effect of the Think Talk Write (TTW) learning model on students' personal letter writing skills. The model's effectiveness is influenced by the teacher's role, student engagement, a conducive classroom atmosphere, and the availability of media and learning resources. Therefore, the Think Talk Write (TTW) learning model is effective in teaching personal letter writing to seventh-grade students at SMP Negeri 24 Surabaya.